An Analysis of Non-Point Source Water Pollution in China and the Economic Policies for Combatting Non-point Source Water Pollution (Global Journal of Science Frontier Research, 2014)
Abstract not found
Keywords: NPS; Chesapeake bay; dianchi lake; PES; BMPs